A new index for frequency stability assessment in Low-Inertia Power Systems - Sishi Qin; Sim Sy Yi; Chao Zhang; Huaying Zhang (PLoS ONE, 2026)
As grid-forming converters (GFM) and grid-following converters (GFL) continue to be integrated into low-inertia power systems in place of traditional synchronous generators, the characteristics and forms of system inertia have undergone significant transformation. This evolution poses significant challenges to conventional inertia response mechanisms and analytical methodologies. To address these challenges, this study proposes a novel grid index frequency stability margin (FSM) from the perspective of frequency stability, encompassing its definition, quantitative evaluation, and practical applications. This paper first introduces the mathematical foundations and operational definitions of the FSM. It then systematically investigates the factors influencing FSM and presents a comprehensive mathematical model specifically developed for low-inertia power systems. The FSM calculation method based on aggregated system modelling was developed, followed by the derivation of a simplified estimation approach suitable for practical engineering applications. The effectiveness of the FSM in analyzing the frequency stability of low-inertia grids was validated through case studies based on provincial-level power grid data from China and a modified IEEE 39-bus system. The findings establish a theoretical framework for optimizing the planning and development of new energy power plants, as well as for formulating grid operation control strategies. This framework offers essential guidance to ensure the secure and stable operation of low-inertia power systems.